(untitled) (The Conference Hub, 2025)
Today, one of the urgent problems of modern nutrition is the need to promote a healthy lifestyle among various segments of the population and create conditions for the prevention of complications of various nutritionally related diseases that arise due to a lack of proteins, animal fats, vitamins and minerals in the daily diet, along with the reduction of the share of negative environmental factors such as dust, various colored drinks, salty and spicy and confectionery products in the diet [1,2,5]. The importance of including foods rich in vitamins A, E, and K, as well as selenium and trace elements in the daily diet of patients with periodontal disease has been emphasized by several authors [1,2]. One of the factors that threatens the quality of life of patients with periodontal disease is the change in healthy eating habits, behavior, culture, and its nutritional and biological value, and its assessment is one of the current issues facing professionals in the field today.